Advanced basic mathematics - Liew, Chin Ying (Penerbit Universiti Teknologi Mara, 2012)
Advanced Basic Mathematics is particularly written for learner who need a thorough understanding in this course. Dow to earth explanation will lead the students through the contents: basic application of differentiation and integration and their application in kinematics, the movement of a particle along a straight line, the basic application of trigonometry in bearing, eangle of elevation and depression and matrices.